The future of EU-ACP cooperation : the end of a historical relationship? - Madeley, John (1998)
Provides a brief overview of the negotiations involved in the preparation of the Lomé Conventions I - IV and looks at the improvement needed in the successor convention from an ACP point of view. Highlights poverty alleviation as pressing need.